Characterization of Ghanaian clays as raw materials for the synthesis of ZSM-5 zeolite - Benjamin K. Kokloku; Johannes A.M. Awudza; Michael B. Mensah; Mizpah A.D. Rockson; Francis Kemausuor (Scientific African, 2025)
Clay minerals are inexpensive and widely available starting materials for the synthesis of zeolites, such as ZSM-5. In this work, clay samples were collected from Anfoega, Mfensi, Teleku-Bokazo, and Tetebu clay reserves in Ghana and used as sources of silica and alumina for the synthesis of ZSM-5 zeolite. The raw clay samples were cleaned, pulverized, and calcined, followed by acid leaching to increase the Si/Al molar ratio, and finally passed through a hydrothermal zeolitization process. Powder-X-ray Diffraction (p-XRD), X-ray fluorescence (XRF), Fourier Transform Infrared spectroscopy (FTIR), and Thermogravimetric Analysis/Differential Scanning Calorimetry (TGA-DSC) were used to characterize the clay samples. All four clay samples contained kaolinite and quartz in addition to other clay minerals. Notably, the pre-treatment processes were key in acquiring the ZSM-5 product. Our results suggest that the controlling factor in making the clay samples viable for the synthesis of ZSM-5 zeolite is the final SiO2/Al2O3 molar ratio obtained after acid leaching. ZSM-5 zeolite was synthesized from all four clay sources at a crystallization temperature and time of 190 °C and 24 h, respectively, demonstrating the potential of the Ghanaian clays as raw materials for zeolite synthesis.